Optimasi Pendistribusian Barang Menggunakan Algoritma Artificial Bee Colony - Irma Surya Kumala Idris (Universitas PGRI Semarang, 2019)
Distribution of goods is one of the important problems for a company. The spread of the customer location and the number of route choices and the absence of an information system application to determine the closest route, have an impact and influence on the distribution process. Delivery of goods carried out on time will increase customer satisfaction. The choice of route in distribution has an effect on the cost and time of travel, where the farther the distance traveled in the delivery of goods will lead to long delivery times resulting in delays in distribution and operational costs will be higher. Based on the settlement, optimization of the distribution process of goods is carried out. This study uses the Artificial Bee Colony algorithm to assist in finding the shortest route. The Artificial Bee Colony algorithm is an optimization algorithm that is considered quite good in the process of finding the shortest route.